12th IFIP/IEEE International Symposium on Integrated Network Management (IM 2011) and Workshops 2011
DOI: 10.1109/inm.2011.5990691
|View full text |Cite
|
Sign up to set email alerts
|

A coordination framework for self-organisation in LTE networks

Abstract: Self-organising Networks (SON) as introduced for 3G Long Term Evolution (LTE) will typically involve several different SON functions. These functions are not necessarily aware of each other and may have complex relations and interdependencies, for example, conflicting parameter settings, depending on their design and approach. Coordination of SON functions may become necessary in order to harmonise the actions of SON functions and allow for a stable and reliablebehaviour of the SON system. This paper describes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 8 publications
(5 reference statements)
0
17
0
Order By: Relevance
“…However, none of these works provide comprehensive identification, annotation and classification of SON function conflicts. Some Self-Coordination mechanisms for SON are described in [9]. However, [9] does not identify the application of these Self-Coordination mechanisms for specific SO function conflicts.…”
Section: Abstract-self-organising Network (Son) Functions Have Been Imentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of these works provide comprehensive identification, annotation and classification of SON function conflicts. Some Self-Coordination mechanisms for SON are described in [9]. However, [9] does not identify the application of these Self-Coordination mechanisms for specific SO function conflicts.…”
Section: Abstract-self-organising Network (Son) Functions Have Been Imentioning
confidence: 99%
“…Some Self-Coordination mechanisms for SON are described in [9]. However, [9] does not identify the application of these Self-Coordination mechanisms for specific SO function conflicts. In [10], for the first time authors have identified and categorised SON function conflicts, based on different criteria such as the network deployment, the Key Performance Indicators, the measurement and logical dependencies, the output parameters' direction/magnitude, etc.…”
Section: Abstract-self-organising Network (Son) Functions Have Been Imentioning
confidence: 99%
“…When they are executed concurrently in the same or different network elements, the impact of their interactions is not easy to be predicted, and unwanted effects may occur. The risk of unacceptable oscillations of configuration parameters or undesirable performance results increase with the number of SON functions, so that it is considered necessary to define and implement a self-coordination framework [3, 4,8].…”
Section: Related Workmentioning
confidence: 99%
“…A preventive coordination mechanism that uses policy-based decisionmaking has been proposed in [10]. Guard functions have been proposed in [4] to detect undesirable network behaviors and trigger countermeasures. Decision trees have been proposed in [20] for properly adjusting remote electrical tilt (RET) and transmission power.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation